Autoeficacia en usuarios de servicios hospitalarios ambulatorios - Robles, Yolanda (2024)
Self-efficacy is a mediatting variable of behavior change in psychosocial interventions for managing health problems. Objective: To establish the level of self-efficacy in the population treated in general hospitals and health centers in Metropolitan Lima and its relationship with common mental problems and prevalent clinical diagnoses. Materials and methods. Study of secondary data from the Epidemiological Study of Mental Health in General Hospitals and Health Centers in Lima-2015. The Schwarzer and Jerusalem General Self-efficacy Scale (GSE) was analyzed in relation to sociodemographic variables, medical specialties, frequent clinical diagnoses, and anxiety, depression, and alcohol abuse/dependence. The data were analyzed with descriptive methods and with inferential methods using tests of independence of means and correlation. Results. The average score of the GSE was 30.89+6.29 and lower in users of the general medicine, psychiatry and neurology specialties, and in the psychology service. Self-efficacy was inversely related to the presence of depression and anxiety, and not to alcohol abuse/dependence. In the six most frequent clinical diagnoses, the GSE score was not different from that shown by all respondents, except in HIV. Conclusions. Self-efficacy varies according to sociodemographic conditions; the mean of the self- efficacy scale in the hospital population is lower than that reported in the general population, and it is lower in depression and anxiety in general than in other clinical pathologies. The convenience of interventions to strengthen the self-efficacy of those attended in the treatment process is highlighted.